(untitled) (Singaporean Journal of Business Economics and Management, 2017)
The paper attempts to outline the South African Presidents State of the Nation address (Sona) delivered to parliament and the nation in February, 2017. In so doing the author posits that, it was a speech that outlined fantasies and outlined very sketchily, what exactly is meant by radical economic transformation. In other words, it coloured the outline of radical economic transformation. Three years running now, the State of the Nation Address has been marred by a riotous assembly that, tells its own story of the state of the nation. After the thunder, the president’s speech was an anti climax and, brought no hope for a beleaguered economy that is reeling and is on a downward spiral. In other words, radical economic transformation as an economic model for South Africa is so wooly, it will be impossible to implement the author contends. This is exemplified by the all embracing reality that Sona talk is cheap and indicates in no uncertain terms that, the African National Congress as the ruling party is full of rhetoric and trips over itself to unpack and decode the phrase radical economic transformation. It has to be realized that, the author posits that after the ratcheted up radical economic transformation rhetoric, the president and finance minister may soon stumble on a terrain potholed by ’alternative facts. The paper therefore looks at the 2017, South African state of the nation address from a critical perspective. At the same time, it looks very briefly at the Finance Minister’s subsequent balanced budget and, the praise that was accorded him, in spite of the attack upon him by the president’s populist acolytes, who want him to be removed, in spite of his sterling performance in most difficult economic times for South Africa.